Did the Student Engage in Academic Dishonesty on their Exam? Yes, No, and Shades of Grey in Decision Making - Goegan, Lauren; Tulloch , Sierra L. P.; Daniels, Lia M. (Canadian Perspectives on Academic Integrity, 2023)
In academia, there are guidelines as to what constitutes academic dishonesty, and how to report it. This leads to the assumption that when instances arise, there are clear yes or no answers to the questions: (a) did the student engage in academic dishonesty, and (b) how should the student be disciplined? Previous research has been conducted examining the behaviours students engage in and the repercussions, but less research has examined the cognitions and actions of the people who discover the instances of academic dishonesty. Therefore, the purpose of this study was to examine how participants make sense of potential academic dishonesty scenarios and the resulting actions they would take. We presented 201 preservice teachers with three scenarios: (a) sneaking answers into an exam, (b) having someone tell you the answers and (c) peeking at someone else’s answers. For each scenario, they had to respond to the items (1) to what extent do you consider the student’s behaviour as academic dishonesty, (2) What in the story helped you decide on your response? and (3) What do you think is an appropriate form of discipline? Overall, participants strongly agreed the behaviours were academically dishonest, however, when asked to indicate what in the story helped them decide, the majority made embellishments to the story, and close to half of the participants provided their opinions related to academic dishonesty more broadly. Moreover, participants indicated a wide range of disciplines for the same scenarios. The results will be utilized to create discussion around decision-making and academic dishonesty.